Dyslexia as a moderator in the relationship between short video learning perception and behavioral intention among Chinese college students: A cross-sectional study - Liu, Tinglei; Yasing, Megat Al Imran; De Costa, Feroz (Elsevier B.V., 2025)
Background: Dyslexia research in China is crucial because of limited awareness, lack of tools, and insufficient support. These issues seriously hinder students' academic success. To address this gap, this study examines how history-related short videos on social media platforms influence the learning behavior of students with dyslexia. This study introduces dyslexia as a moderating variable within the Technology Acceptance Model (TAM) framework for the first time, addressing a significant gap in understanding how learning differences influence technology adoption in educational contexts. History poses special challenges for learners with dyslexia because it requires extensive reading and complex texts. Short videos may offer a more accessible and engaging alternative. Methods: A cross-sectional study was conducted among 400 university students in Hebei province, China using a self-administered questionnaire. Several scales were used in the survey: Quality of Content (CQ), Perceived Ease of Use (PEOU), Perceived Usefulness (PU), Behavioral Intention (BI), Dyslexia Scale, and Learning Behavior (LB). Descriptive statistics and structural equation modeling (SEM) analyses were performed. A P value of <0.05 was considered significant. Results: The results show positive correlations among key variables. Content quality was positively correlated with perceived usefulness (r = 0.369), perceived ease of use (r = 0.329), and behavioral intention (r = 0.203), all p < 0.01. Ease of use is also associated with usefulness (r = 0.323), and usefulness with intention (r = 0.249). Learning intention further predicts behavior (r = 0.359). However, the direct link between ease of use and behavioral intention is not significant (p = 0.17). Dyslexia significantly moderates the relationship between PEOU and PU (p < 0.001). However, it does not significantly affect the relationships between (1) PEOU and BI or (2) PU and BI, though these effects approach marginal significance. Conclusions: Students with dyslexia show different levels of learning intention depending on content quality, ease of use, and usefulness. Dyslexia significantly moderates some of these relationships. The findings suggest that history-related short videos can be effective educational tools, especially when they emphasize usability and usefulness.